Research on the Prediction of Concealed Uranium Deposits Using Geo-Electrochemical Integrated Technology in the Guangzitian Area, Northern Guangxi, China - Xiaohan Zhang; Meilan Wen; Qiaohua Luo; Yunxue Ma; Yuheng Jiang; Yuxiong Jiang; Wei Ye; Jiali Zhang (Applied Sciences, 2025)
To achieve a significant breakthrough in the exploration of uranium resources in the Guangzitian area of northern Guangxi, China, an innovative combination of exploration methods was implemented at the peripheral regions of the Guangzitian uranium deposit under the guidance of the following principle: “exploring the edges and identifying the bottom, delving deep and un-covering blind spots”. This study introduces geo-electrochemical integrated technology for prospecting research at the peripheral areas of the Guangzitian deposit. By validating the technology’s effectiveness on known geological sections, distinct geo-electrochemical extraction anomalies were identified above recognized ore bodies. Simultaneously, soil ionic conductivity and thermally released mercury anomalies were observed, partially indicating the presence of concealed uranium deposits and fault structures. These findings demonstrate that geo-electrochemical integrated technology is effective in detecting buried uranium mineralization in this region. Subsequently, a geological-geoelectrical prospecting model was established through a systematic analysis of anomaly characteristics and metallogenic regularity, and it was subsequently applied to unexplored areas. As a result, one key anomaly verification zone, one Class A comprehensive anomaly zone, two Class B comprehensive anomaly zones, and one Class C comprehensive anomaly zone were identified within the unexplored research area. Drilling engineering validation was conducted in the No. Ι key anomaly verification zone, resulting in the discovery of an industrial-grade uranium ore body. This achievement not only provides critical technical support but also develops a robust theoretical foundation for future mineral exploration endeavors.